Assessing the Accuracy of College Students’ Summary Writing - Yosep Hendrian (Universitas Pendidikan Indonesia (UPI), 2013)
The study reported the investigation the ability of students’ summary writing. The respondents in this article were students of English Education Department in one state university in Bandung. The respondents were given three different levels of topics to be summarized, and then the students’ summary writing was scored. In general, the results showed that most of the students have good ability to summarize the topics. It can be seen that most the students’ summary writing scores were good and excellent.Keywords: Writing, Summary Writing, Academic Writing, Assessment